Vermicompost Supply Modifies Chemical Composition and Improves Nutritive and Medicinal Properties of Date Palm Fruits From Saudi Arabia - Al Jaouni, Soad; Selim, Samy; Hassan, Sherif H.; Mohamad, Hussein S. H.; Wadaan, Mohammed A. M.; Hozzein, Wael N.; Asard, Han; AbdElgawad, Hamada (Frontiers in Plant Science, 2019)
To meet the increased demand for phytochemicals, plant cultivation in soil amended with biofertilizers has been developed. Here, we aimed to use vermicompost as an environmentally safe biofertilizer to enhance the nutritive and medicinal value of five common cultivars of Saudi date palm; namely Phoenix dactylifera L. var. Ajwa, Hulwa, Ruthana, Sefri, and Luban. To determine changes in the fruit nutritive composition, primary metabolites, antioxidants, phenolic compounds and mineral profiles were analyzed in the fruits from non-fertilized and vermicompost-fertilized date palms. We also tested how changes in the fruit chemical compositions due to vermicompost fertilization affected their medicinal potentials. Applying vermicomposts generally increased primary metabolites, vitamins, and mineral content as well as the medicinal potential of the date palm fruits. This positive effect is possibly explained by the role of vermicomposts in improving soil health and fertility. Furthermore, clustering analyses and principal component analysis (PCA) indicated cultivar-specific responses. PCA analysis also revealed that the bioactivities of the date palm fruit extracts and their antioxidants tended to display correlated output values. One of the highly accumulated phenolic compounds, β-D-glucogallin, was extracted and purified from P. dactylifera L. var. Ajwa fruits and showed significant antioxidant, anticancer, antibacterial, antimutagenic, and antiprotozoal activities. Overall, applying vermicompost is an innovative approach to increase the nutritive quality and medicinal potential of date palm fruits.